Synthesis of Cu2ZnSnS4 Thin Films by a Precursor Solution Paste for Thin Film Solar Cell Applications - Cho, Jin Woo; Ismail, Agus; Park, Se Jin; Kim, Woong; Yoon, Sungho; Min, Byoung Koun (American Chemical Society, 2013)
Cu2ZnSnS4 (CZTS) is a very promising semiconductor material when used for the absorber layer of thin film solar cells because it consists of only abundant and inexpensive elements. In addition, a low-cost solution process is applicable to the preparation of CZTS absorber films, which reduces the cost when this film is used for the production of thin film solar cells. To fabricate solution-processed CZTS thin film using an easily scalable and relatively safe method, we suggest a precursor solution paste coating method with a two-step heating process (oxidation and sulfurization). The synthesized CZTS film was observed to be composed of grains of a size of similar to 300 nm, showing an overall densely packed morphology with some pores and voids. A solar cell device with this film as an absorber layer showed the highest efficiency of 3.02% with an open circuit voltage of 556 mV, a short current density of 13.5 mA/cm(2), and a fill factor of 40.3%. We also noted the existence of Cd moieties and an inhomogeneous Zn distribution in the CZTS film, which may have been triggered by the presence of pores and voids in the CZTS film.